2000
DOI: 10.1091/mbc.11.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coordination of Three Mitotic Motors inDrosophilaEmbryos

Abstract: It is well established that multiple microtubule-based motors contribute to the formation and function of the mitotic spindle, but how the activities of these motors interrelate remains unclear.Here we visualize spindle formation in living Drosophila embryos to show that spindle pole movements are directed by a temporally coordinated balance of forces generated by three mitotic motors, cytoplasmic dynein, KLP61F, and Ncd. Specifically, our findings suggest that dynein acts to move the poles apart throughout mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
296
5
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(335 citation statements)
references
References 63 publications
(85 reference statements)
31
296
5
3
Order By: Relevance
“…Mouse-anti-P10 (Dick et al, 1996) at 1/500 and rat-anti-DDLC1 at 1/200 (Ghosh-Roy et al, 2004) were used for the immunolocalization of DDLC1. The monoclonal anti-DHC (Sharp et al, 2000) and polyclonal anti-Shibire (Estes et al, 1996) were used at 1/10 and 1/200 dilutions, respectively. …”
mentioning
confidence: 99%
“…Mouse-anti-P10 (Dick et al, 1996) at 1/500 and rat-anti-DDLC1 at 1/200 (Ghosh-Roy et al, 2004) were used for the immunolocalization of DDLC1. The monoclonal anti-DHC (Sharp et al, 2000) and polyclonal anti-Shibire (Estes et al, 1996) were used at 1/10 and 1/200 dilutions, respectively. …”
mentioning
confidence: 99%
“…On the other hand, injection of dynein antibodies or overexpression of human p50 dynamitin in Drosophila syncytial embryos was reported to affect chromosome movement by impairing both anaphase A and B [96,97]. However, from these studies and due to the rapid syncytial divisions, it was not clear whether the observed effects on anaphase A were truly due to a requirement for kinetochore dynein in chromosome movement or to an indirect effect caused by "forced" mitotic exit.…”
Section: Kinetochore Dyneinmentioning
confidence: 98%
“…separation of spindle poles by cortical mediated pulling forces on astral microtubules), also known as anaphase C [212]. The microtubule sliding mechanism proposed by McIntosh and colleagues (1969) explains at least part of the spindle elongation in many systems, including diatoms, yeasts and Drosophila embryos [96,[213][214][215][216]. At the molecular level, the players involved in each system might be different, although their modus operandi must be essentially the same: cross-linking, sliding and eventually growth/stabilization of interpolar microtubules of opposite polarity.…”
Section: Anaphase a Vs Anaphase Bmentioning
confidence: 99%
See 2 more Smart Citations